The agitated older adult in the emergency department: a narrative review of common causes and management strategies - Maura Kennedy; Jennifer Koehl; Christina L. Shenvi; Allyson Greenberg; Olivia Zurek; Michael LaMantia; Alexander X. Lo (Journal of the American College of Emergency Physicians Open)
Abstract Agitation and aggression are common in older emergency department (ED) patients, can impede the expedient diagnosis of potentially life‐threatening conditions, and can adversely impact ED functioning and efficiency. Agitation and aggression in older adults may be due to multiple causes, but chief among them are primary psychiatric disorders, substance use, hyperactive delirium, and symptoms of dementia. Understanding the etiology of agitation in an older adult is critical to proper management. Effective non‐pharmacologic modalities are available for the management of mild to moderate agitation and aggression in patients with dementia. Pharmacologic management is indicated for agitation related to a psychiatric condition, severe agitation where a patient is at risk to harm self or others, and to facilitate time‐sensitive diagnostic imaging, procedures, and treatment. Emergency physicians have several pharmacologic agents at their disposal, including opioid and non‐opioid analgesics, antipsychotics, benzodiazepines, ketamine, and combination agents. Emergency physicians should be familiar with geriatric‐specific dosing, contraindications, and common adverse effects of these agents. This review article discusses the common causes and non‐pharmacologic and pharmacologic management of agitation in older adults, with a specific focus on dementia, delirium, and pain.